The devil's diary : Alfred Rosenberg and the stolen secrets of the Third Reich - Wittman, Robert K. (William Collins, 2016)
An unprecedented, page-turning narrative of the Nazi rise to power, the Holocaust, and Hitler's post-invasion plans for Russia told through the recently discovered lost diary of Alfred Rosenberg - Hitler's `philosopher' and architect of Nazi ideology